2019
DOI: 10.1108/jsma-07-2019-0130
|View full text |Cite
|
Sign up to set email alerts
|

Building blocks for the development of an IoT business model

Abstract: Purpose Previous studies have identified a variety of Internet of Things (IoT) business models and have recognised the complexity related to the application of IoT technologies in business, along with the potential of the modularity concept application in organisational design. The purpose of this paper is to identify the main building blocks for the development of a business model canvas for companies that adopt the IoT in their business. Design/methodology/approach First, the authors carried a systematic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…It is interesting to notice how the theoretical supposition that companies would have needed to define new IoT-based business models, put forward in the oldest articles of this group (e.g. Dominici et al, 2016), has become one of the core debates surrounding IoT, to the point that the design of the BM is considered as one of the most important challenges associated to the use of IoT (Almeida et al, 2020). Indeed, on the one hand, IoT allows offering products and their new functionalities as services, and on the other hand, data collected through connected devices can be used as inputs to improve internal processes (Leminen et al, 2018).…”
Section: Cluster 4: Iot Servitization and Business Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to notice how the theoretical supposition that companies would have needed to define new IoT-based business models, put forward in the oldest articles of this group (e.g. Dominici et al, 2016), has become one of the core debates surrounding IoT, to the point that the design of the BM is considered as one of the most important challenges associated to the use of IoT (Almeida et al, 2020). Indeed, on the one hand, IoT allows offering products and their new functionalities as services, and on the other hand, data collected through connected devices can be used as inputs to improve internal processes (Leminen et al, 2018).…”
Section: Cluster 4: Iot Servitization and Business Modelsmentioning
confidence: 99%
“…These contributions stress that value is created by an ecosystem rather than by a single firm, as also Industry 4.0 and business models: a review confirmed by Hakanen and Rajala (2018), who make a practical example of how material intelligence allowed by IoT can change the way firms in the steel industry create value. The connection between ecosystems and business model types has been stressed in the recent literature on IoT (Leminen et al, 2018;Almeida et al, 2020), and this calls for widening the current business model thinking from a single company point of view to an ecosystem perspective.…”
Section: Cluster 4: Iot Servitization and Business Modelsmentioning
confidence: 99%
“…Most of the business models noted by the literature include blocks or sets of elements with operational roles, but there is no consensus on how canvas should be (Canestrino, et al, 2019). Some authors prefer to call it building blocks, components or just elements, although the former is the most commonly used (Almeida, et al, 2019). Building blocks provide a way to set the framework of a business model and define logic to generate profits for the company, as well as develop and deliver value to customers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Osterwalder and Pigneur in (Müller, 2019), the canvas business model consists of nine blocks that help one formulate a business idea into a business model (Almeida, et al, 2019;Canestrino, et al, 2019;Carter & Carter, 2020;Ojasalo & Ojasalo, 2018). Here are nine blocks on the business model canvas e.g., Customer Segments, the customer segment block describes a group of different people or organizations that the company wants to reach or serve.…”
Section: Business Model Canvasmentioning
confidence: 99%
“…Tailings dam failures all around the World, caused irreparable losses, which, for the most occurred in developing countries (Almeida et al, 2019a;Lyu et al, 2019). A recent example that illustrates the importance of this is the Brumadinho Dam disaster, a tailings dam of iron ore mine in Brazil, which occurred in January 2019 and left behind a considerable number of fatalities, with damages on the environment and the local economy (Almeida et al, 2019b). According to the usual reasons for dam failures, (Sun et al, 2012) presented a significant model for Tailings Dam Monitoring and Pre-Alarm System (TDMPAS) based on IoT and Cloud Computing (CC).…”
Section: Predictable Mining Operationmentioning
confidence: 99%